Bayam bite / Nurulhuda Zoli, Damia Mahadzir and Syarifah Mahani Syed Syahrill - Zoli, Nurulhuda; Mahadzir, Damia; Syed Syahrill, Syarifah Mahani (2017)
BAYAM BITE is a business that involves in process of innovation and new venue creation through four dimensions which include individual, organization, environment, and institution. Entrepreneurs are individuals who actively form are lead by their own business nurture them for growth and prosperity. In order to form a business, there are quite a number of phases that should be understood and developed by the entrepreneur. BAYAM BITE is a business developed to present flavored snack product. This business is. a partnership in which -venture of 3 partners. Each partner assist in contributing capitals of RM 2556; except for the Financial Manager who contribute RM10056. Each of the partner members ill hold different positions n and responsible in managing this business. BAYAM BITE is a business that mainly focuses on producing bayam chips' with different flavours. We discover that Malaysian people love to eat snacks but at the same time they want to have a good health. Therefore, our partners have decided to build up this business. Besides that, all snacks produced by BAYAM BITES is suitable for all Malaysian people regarding their age, gender and religion. Finally, we are planning to expand. Malaysia's Small and Medium Enterprise (SME) through this field of business and we aim to become one of Malaysia's young and leading entrepreneur in the food industry through the breakthrough of the product in the international market.